2020
DOI: 10.1071/sh20154
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, HIV conspiracy theories and pre-exposure prophylaxis acceptability in gay men

Abstract: Background Combination prevention, which includes pre-exposure prophylaxis (PrEP), is essential for achieving the zero HIV infections target in the UK by 2030. It is important to assess attitudes towards PrEP in at-risk populations. This study focuses on the effect of discrimination and HIV conspiracy theorising on attitudes towards PrEP in gay men in the UK. Methods: In total, 244 White British gay men completed a survey that included demographic questions and measures of sexual health screening, hypervigilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Some may have long-term exposure to homonegativity due to dominant negative social representations in their social environment. Jolley and Jaspal (2020) found that gay men who are hypervigilant to discrimination are more likely to report its existence, possibly because previous experiences of discrimination have primed them to anticipate it in the future. Gay men who face discrimination may come to believe that people in their social context have negative and hostile views about their community (Castro et al, 2019).…”
Section: Homonegativitymentioning
confidence: 98%
See 2 more Smart Citations
“…Some may have long-term exposure to homonegativity due to dominant negative social representations in their social environment. Jolley and Jaspal (2020) found that gay men who are hypervigilant to discrimination are more likely to report its existence, possibly because previous experiences of discrimination have primed them to anticipate it in the future. Gay men who face discrimination may come to believe that people in their social context have negative and hostile views about their community (Castro et al, 2019).…”
Section: Homonegativitymentioning
confidence: 98%
“…H5: It has been found that the actual experience of discrimination is associated with the anticipation of further stigma in sexual minorities (Castro et al, 2019) due partly to a hypervigilance effect (Jolley & Jaspal, 2020). Therefore, everyday discrimination should be associated with perceived negative social representations of gay men.…”
Section: A Theoretical Model Predicting Internalised Homonegativitymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be rooted in the perception that one's sexuality is not accepted by others (especially by significant others) and that one's value as a gay man is thus questionable and in the possible anticipation of negative experiences upon future sexual identity disclosure (Ryan et al, 2015;Weinstein et al, 2012). The latter has been referred to as hypervigilance and is characterized by negative psychological outcomes, such as avoidance behaviours (Jolley & Jaspal, 2020). Incidentally, this line of thinking is also consistent with the empirical observation in our study that internalized homonegativity is positively associated with both distress and identity threat.…”
Section: Discussionmentioning
confidence: 99%
“…However, to understand this relationship further, we examine the potential mediating role of an additional variable which taps into the perceived typicality of one's coming out experience of one's overall coming out experiences. After all, a negative coming out experience which is deemed to be more typical is likely to reinforce the view that opposition to one's sexuality is consensual and commonplace (Jolley & Jaspal, 2020); it may induce uncertainty and fear in relation to future and present, and therefore result in greater feelings of distress (Burgess et al, 2007). We therefore predict that the relationship between recalling a negative coming out experience and distress will be mediated by the perceived typicality of the recalled coming out experience, with greater typicality being associated with greater distress.…”
Section: Coming Out and Subsequent Recallmentioning
confidence: 99%